MODELS GENERATED IN NEUTRON PROBE CALIBRATION IN LATOSOL CULTIVATED WITH COFFEE AND SIGNALGRASS - Borges, Inácio Barbosa; Rocha, Omar Cruz; Malaquias, Juaci Vitória; Fagioli, Marcelo; Sá, Marcos Aurélio Carolino de; Guerra, Antônio Fernando (Coffee Science - ISSN 1984-3909, 2018)
ABSTRACT: The sustainability of agricultural production can be improved through the use of cover crops. The objective of this study was to evaluate the Model Identity Method in the verification of equality of linear regressions resulting from the calibration of a neutron probe for different layers, as a function of signalgrass management as a cover crop between rows of soil coffee crop in the Brazilian Central Cerrado. Aluminum tubes were installed to access the probe and two saturation basins were built in a coffee area, irrigated by a central pivot, in an Oxisol, with two management systems, T (Traditional with bare soil) and B (Signalgrass in the row). Samples were taken at depths of 0-0.20; 0.20-0.40; 0.40-0.60; and 0.60-0.80 m for the determination of physical and water properties and monitoring of soil drying; concomitant measurements were taken with the neutron probe in these layers. Two calibration curves were constructed for each layer, which were compared by the above method. It was observed that treatment B yielded differences in soil water storage in the 0.20-0.40 m layer, differing from treatment T. The statistical method allowed the observation of equality of regressions between treatments B and T at depths 0-0.20, 0.40-0.60, and 0.60-0.80 m; it also showed the need for different regression curves per layer, besides justifying the need for neutron probe calibration for each specific local condition.